(untitled) (Journal of Dentistry and Allied Science, 2025)
Background: Evidence suggests that implementation of color-coded systems for waste segregation is an inexpensive and effective method for improving compliance and achieving sustainable waste management. This narrative review examines practices and experiences from other parts of the world to appreciate the challenges and leverage points in the context of waste management in Bangladesh. Methods: A narrative review was performed in the period of January 2006 to January 2025, using PubMed and Google Scholar. The review incorporated literature in the areas of segregation of biomedical and dental waste, color-coded waste management systems, and compliance and adherence to waste management in low and middleincome countries (LMICs). The policy documents issued by the WHO, CDC, and national environmental authorities were also analyzed. Thematic analysis was utilized to examine the global waste management frameworks, practices in various regions, and the implementation shortcomings in Bangladesh. Results:In high-income countries, compliance with color-coded segregation systems is nearly 90% owing to regulation, training, and digital monitoring for compliance. Whereas, LMICs and South Asia, compliance is only 60-80% because of poorly trained personnel and weak enforcement. The 2008 Medical Waste Management Rules in Bangladesh implemented color-coded segregation of waste (yellow, red, blue, and black bins), but compliance in dental practices still remains inconsistent.Staff training, standardized labeling, and monitoring, at the institutional level, have been shown to assist in compliance. Conclusion: Evidence-sustainably supports the use of color-coded segregation for the effective management of dental waste. In the case of Bangladesh, implementation necessitates compulsory training and monitoring, incorporation into dental curricula, and enforcement of regulations. The use of the segregations as proposed by the WHO will enable safe dental practices while shielding health workers, the population, and the environment, thus enjoyed safe and sustainable systems. Journal of Dentistry and Allied Science, Vol. 8 No 2: 77-85